Pengaruh Kepadatan Penduduk Terhadap Produk Domestik Regional Bruto (PDRB) Per Kapita Provinsi Jawa Barat Tahun 2022 - Tengku Abdillah Azis; Andreas Sito Saputra; Salma Nur Azkiya; Carissa Windiati (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
This study delves into the correlation between population density and Gross Regional Domestic Product (GRDP) in West Java Province during 2022. Employing a quantitative approach, the analysis utilizes pertinent statistical data from the West Java Province Central Statistics Agency. Employing a descriptive correlational design, this research employs a simple linear regression method to scrutinize the relationship between population density and GRDP. The analysis findings reveal a feeble connection between population density and GRDP, with population density exerting a mere 2.7% influence on GRDP. These findings underscore the role of other factors such as Human Resources (HR), Natural Resources (NR), and regional topography in determining the GRDP level of a region.